153k views
4 votes
Hi I really need help on how to solve this step by step as I am very confused like i also don’t know if my answer 72 is done correctly.

Hi I really need help on how to solve this step by step as I am very confused like-example-1
User Cviejo
by
5.2k points

1 Answer

5 votes

solution:

case: functions

Method:

a)


\begin{gathered} (f\circ g)(5) \\ f(g(5)) \\ \Rightarrow g(5)=-2 \\ Hence \\ f(g(5)) \\ \Rightarrow f(-2)=-5(-2)^2-4(-2)-5 \\ f(-2)=-5*4-4(-2)-5 \\ f(-2)=-20+8-5 \\ f(-2)=-17 \end{gathered}

b)


\begin{gathered} (g\circ f)(0) \\ g(f(0)) \\ \Rightarrow f(0)=-5(0)^2-4(0)-5 \\ f(0)=-5 \\ Hence \\ g(f(0)) \\ \Rightarrow g(-5) \\ g(-5)=-4x+2 \\ g(-5)=-4(-5)+2 \\ g(-5)=20+2 \\ g(-5)=22 \end{gathered}

Final answer:


\begin{gathered} a)\text{ }(f\circ g)(5)=-17 \\ b)\text{ }(g\circ f)(0)=22 \end{gathered}

User Scott Z
by
5.4k points